Ғ. МҰСТАФИН ШЫҒАРМАЛАРЫНДАҒЫ МАҚАЛ-МӘТЕЛДЕРДІҢ, АФОРИЗМДЕРДІҢ КЕЙІПКЕР ТІЛІНДЕ ҚОЛДАНЫЛУЫНЫҢ МӘДЕНИ ҰЛТТЫҚ СЕМАНТИКАСЫ - Қанапина, С.Ғ. (My University, 2018)
В статье рассматривается национально-культурная семантика афоризмов, пословиц и поговорок в речи героев произведений Г. Мустафина.
NATIONAL-CULTURAL SEMANTICS OF APHORISMS, PROVERBS AND SAYINGS IN THE SPEECH OF THE HEROES OF WORKS BY G. MUSTAFIN
Keywords: речь героя; афоризм; пословицы и поговорки; образность; философская мысль; speech of the hero; aphorism; proverbs and sayings; imagery; philosophical thought